KAJIAN IKONOGRAFI DESAIN GRAFIS BERGAYA SUREALISTIK PADA T-SHIRT MEREK WELLBORN KOLEKSI TAHUN 2017 DI BANDUNG - Siti Hadiyanti; Naomi Haswanto; Achmad Haldani Destiarmand (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2019)
Local brand is a fashion creative industry which is favored by young people. There are many local brands in Bandung City. T-shirt is one of local brand products which is related to graphic design. Concept and meaning in graphic design on T-shirt can be researched using The Iconography Theory of Erwin Panofsky. Graphic design on local brands T-shirt in Bandung City leads to simple graphic design trends, display direct branding and variation of color in T-shirts. However, one of brand, Wellborn, features graphic design with its own characteristics on the T-shirt as a creativity, that is surrealistic style graphics design on T-shirt. It is a sub category of T-shirt that can be studied through the meaning of graphic design on T-shirt. It underlies the research on graphic design of Wellborn T-shirt. The research stages are observation, interview, literature study, documentation and analysis which includes pre-iconography, iconography and iconology. The purpose of this study is to know the meaning of Wellborn T-shirt design based on The Iconography Theory of Erwin Panofsky and its association with Wellborn branding. The research method is descriptive qualitative. Objects studied are the surrealistic style graphic designs of Wellborn T-shirts 2017 collection. The samples of data are selected using purposive sampling. The result of the analysis shows that in pre-iconography, there are various objects placed in one graphic design on T-shirt. In iconography, it has a secondary meaning that there are things which are limitless, and in iconology, it has the meaning of freedom of mind/thought because it is related to freedom in imagination, infinity and a difference. They show the characteristics of the Wellborn brand. Keywords: Iconography, Graphic Design, Surrealistic Wellborn T-shirt, Bandung.